Leadership and gender in the public sector: the mediating effect of job satisfaction / Fadilah Puteh, NurSyazwani Mohamad and ‪Sharifah Syahirah Syed Sheikh‬ - Puteh, Fadilah; Mohamad, NurSyazwani; Syed Sheikh‬, Sharifah Syahirah (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Topics on gender and leadership style have attracted many researchers from various field of study particularly in psychology and management discipline. Gender and leadership is one of the most controversial issues especially in the public sector organizations. Furthermore, research that focus on gender role is scarce in Malaysia particularly in an enforcement agency. Women are found to be struggling to exercise effective leadership style in an agency that is highly perceived as masculine position. The constructs of the study were adapted from Korabik and Ayman Multi-Perspective Model of Gender and Leadership (2007). The model consists of three (3) main variables namely intrapsychic process, social structural, and interpersonal interactions. The objectives of this paper are threefold: (1) to examine the level of employee acceptance towards male and female bosses; (2) to examine the effect of intrapsychic process, social structural, and interpersonal interactions against employee acceptance towards male and female bosses; and (3) To examine the mediating effect of job satisfaction between intrapsychic process, social structural, and interpersonal interactions on employee acceptance towards male and female bosses. Data were collected through structured questionnaire from 300 samples of employees in Royal Malaysia Police (RMP) Pahang Headquarter ranging from sub-inspector rank and below to represents the population for this study. Findings obtained in this study revealed that the level of employees’ acceptance towards their bosses is at moderate level. It was also found that social structural is the most influential predictor of employee acceptance towards their leader. Further analysis also found that job satisfaction is a significant mediator.